Graphene Oxide Aerosol Deposition and its Influence on Cancer Cells. Preliminary Results - Nasiłowska, Barbara (Materials (Basel), 2020)
This paper presents the results of the interaction of graphene oxide (GO) on MDA-MB-231 and SW-954 cancer cell lines. The tests were carried out in two variants. In the first one, GO was sprayed on a Petri dish and then, the cancer cell lines were cultured. In the second variant, the cells were covered with an aerosol containing GO. In both variants, cancer cell lines were incubated and tested every 24, 48, and 72 h. After each time period, cell viability and surface morphology were measured. The tests after 72 h showed that coating with GO aerosol caused a reduction in cell viability by 52.7% and 26.4% for MDA-MB-231 and SW-954 cancer cell lines, respectively, with respect to a reference sample (without the influence of GO aerosol). Tests where GO is a culture medium demonstrated a decrease in cell viability by approximately 4.3% compared to a reference sample for both considered cell lines.